Risk perception and coping strategy taken by flood victims in Kuching division, Sarawak, Malaysia - Nazibah, Baharin; Rahman, M.M. (Medip Academy, 2021)
Background: Nine per cent of the total areas of Malaysia is subjected to flood. The individual’s risk perception is one of the fundamental values in determining the subsequent behaviour, action, coping mechanism and effective strategy towards possible risk. Thus, this study aims to determine the risk perception and coping strategy among the flood victims in Kuching, Sarawak, and its factors. Methods: The 200 respondents were systematically selected from three districts in Kuching division, Sarawak. Data were collected through face-to-face interviews using interviewer-administered questionnaire. Results: The analysis revealed that about three-fifths (72.5%) of the respondents were inundated last year. The most definite perceptions of risk by the flood victims were a physical health risk, followed by the capacity to mitigate flood and the perception of the social consequences. The respondents had a moderate (score of 4 to 6) to good (score of 7 to 9) level of coping strategy, which was influenced by ethnicity and level of education (p<0.05).Conclusions: Though the flood risk perception was good, it needs to go hand-in-hand with the coping measures to minimise flood impact. The planning for flood-related health programs and activities should be more community-centred by assigning villagers and the vulnerable group as committee members.